Tucker, Judith E. In the House of the Law: Gender and Islamic Law in Ottoman Syria and Palestine. Berkeley, Los Ángeles, Londres: University of California, 2000. 229 p. - Western, Wilda Celia (El Colegio de México, 2001)
-